143 Persistent Rotating Shift Work Is a Second Hit Contributing to Abnormal Liver Function among On-Site Workers Having Fatty Liver. (11th October 2013) - Chen, P C; Lin, Y C
Abstract : Objective: To investigate the relationship between elevated serum alaninetransaminase (ALT) and persistent rotating shift work (p-RSW) among employees with sonographic fatty liver (SLF). Methods: The authors performed a retrospective analysis on a cohort of electronics manufacturing workers. The records of 758 workers (507 males, 251 females) with initially normal ALT and a mean age of 32.9 years were analysed. Results: A total of 109 workers (14.4%) developed elevated ALT (e-ALT) after five years. Compared with those having neither initial SFL nor p-RSW exposure, multivariate analysis indicated that employees who had initial SFL but without p-RSW finally had a higher risk (odds ratio: 2.9; 95% confidence interval (CI): 1.7–5.1) for developing e-ALT; workers with baseline SFL plus p-RSW had a 3.7-fold increased risk (95% CI: 1.8–7.5). Conclusions: SFL poses a conspicuous risk for the development of e-ALT, and persistent p-RSW exposure significantly aggravates the development of e-ALT among on-site workers with preexisting SLF.